A Review Paper on Raspberry Pi (International Journal of Current Engineering and Technology, 2014)
The Raspberry Pi is a very powerful computer having the dimensions of a business card. In this paper we review Raspberry Pi whose popularity has taken the learning process and application of ideas to a whole new level. We also discuss some of the best projects that have come up so far.
Keywords: Raspberry Pi; Business card etc.